2008
DOI: 10.1095/biolreprod.107.064022
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Adrenomedullin and Its Receptors in the Reproductive System of the Rat: Effects on Steroid Secretion in Rat Ovary1

Abstract: The present study demonstrates the expression of adrenomedullin (ADM) in the reproductive system of the female rat and its effect on the secretion of estradiol and progesterone. Ovarian ADM and Adm mRNA levels were decreased at estrus, whereas oviductal Adm mRNA levels were low at proestrus. Both tissues were shown to coexpress mRNAs encoding the calcitonin receptor-like receptor and receptor activity-modifying protein 1 (Ramp1), Ramp2, and Ramp3. Gel filtration chromatography of ovarian extracts showed two pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
1
31
1
Order By: Relevance
“…We have demonstrated a high expression of ADM peptide and mRNA (Li et al 2008) and an action of ADM on ciliary beat in the rat oviduct. This suggests that ADM is a potential factor to affect oviductal function.…”
Section: Introductionmentioning
confidence: 78%
“…We have demonstrated a high expression of ADM peptide and mRNA (Li et al 2008) and an action of ADM on ciliary beat in the rat oviduct. This suggests that ADM is a potential factor to affect oviductal function.…”
Section: Introductionmentioning
confidence: 78%
“…Studies of ADM and CGRP in rat ovaries have shown that although CGRP is confined to nerve endings [141, 142], ADM expression in ovarian follicles increases from the small antral stage to the large antral stage and corpora lutea. In addition, levels of ADM in ovarian follicles and the corpora lutea vary during the estrous cycle [1719, 21], and the ADM level in the corpus luteum is higher in late pregnancy compared to early pregnancy [24]. Although CGRP appeared to have no effect on the basal or follicle-stimulating hormone (FSH)-stimulated release of estradiol or progesterone from cultured rat granulosa cells [141], ADM and IMD stimulated cAMP and estradiol production in cultured granulosa cells [143] (Fig.…”
Section: Role Of Clr/ramp Receptor Signaling In the Ovarymentioning
confidence: 99%
“…ADM, CGRP, IMD, and their receptors are highly conserved across species [1315], and are expressed in female reproductive organs including the ovaries, oviducts, and uterus as well as the placenta [1621]. During the evolution of placental reproduction in therian mammals, these con-served peptides and receptors were recruited to perform new regulatory functions that originated in the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the presence of sperm up-regulates the expression of oviductal ADM in mice, suggesting a possible physiological role of ADM in this part of the female genital tract (13). Previous work in our group has demonstrated the expression of ADM peptide and mRNA in rat oviduct by immunohistochemistry and RT-PCR (11,14). In humans, our preliminary work (15) also showed that ADM in the human oviduct varied in its levels with the hormonal cycle, stimulated ciliary motility of the human oviduct and was up-regulated by contact with sperm.…”
mentioning
confidence: 88%